Isolation and typing of Streptococcus mutans and Streptococcus sobrinus from caries-active subjects - Hamzah Abdulrahman Salman; R Senthilkumar; Khalid Imran; K Panneer Selvam (Wolters Kluwer Medknow Publications, 2017)
Background: Streptococcus mutans and Streptococcus sobrinus are main etiological agents of dental caries. Aim: The aim of the study was to isolate, identify, characterize, and determine the minimum inhibitory concentration (MIC) of S. mutans and S. sobrinus from caries-active subjects. Materials and Methods: Sixty-five plaque samples were collected from caries-active subjects aged between 35 and 44 years, processed and cultured on mitis salivarius bacitracin agar. All the bacterial isolates were subjected to morphotyping and the suspected colonies were identified by 16S rDNA sequencing. The S. mutans and S. sobrinus strains were characterized by biotyping and phylogenetic analysis. The MIC of ampicillin and erythromycin was determined by microtiter plate method. Results: Of the study population, 41 isolates displayed typical colony morphologies of S. mutans and S. sobrinus. The 16S rDNA sequencing results revealed that 36 isolates were S. mutans and 5 isolates were S. sobrinus. The biotyping of these isolates demonstrated three biotypes, namely, biotype I (n = 35), biotype III (n = 1), and biotype IV (n = 2). However, 3 isolates exhibited variant biotypes. The phylogenetic analysis revealed that the clinical strains of S. mutans and S. sobrinus clustered independently along with respective reference strains. The average MIC of ampicillin and erythromycin against S. mutans and S. sobrinus was 0.047 μg/ml and 0.39 μg/ml, respectively. Conclusion: The 16S rDNA sequencing was an impeccable method for S. mutans and S. sobrinus identification when compared with morphotyping and biotyping methods. The study also suggested that nonspecific bacteria might be involved in caries formation.